2002
DOI: 10.1182/blood.v100.4.1160.h81602001160_1160_1167
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase processing of monocyte chemoattractant proteins generates CC chemokine receptor antagonists with anti-inflammatory properties in vivo

Abstract: Monocyte chemoattractant protein (MCP)–3 is inactivated upon cleavage by the matrix metalloproteinase (MMP) gelatinase A (MMP-2). We investigated the susceptibility to proteolytic processing of the 4 human MCPs by 8 recombinant MMPs to determine whether MCP-3 is an isolated example or represents a general susceptibility of chemokines to proteolytic inactivation by these important inflammatory proteases. In addition to MMP-2, MCP-3 is efficiently cleaved by membrane type 1 (MT1)–MMP, the cellular activator of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
239
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(255 citation statements)
references
References 38 publications
8
239
1
5
Order By: Relevance
“…Conceptually, these findings showed that MMPs can not only act as effectors but also regulators of inflammatory responses [47]. Subsequently, CCL7 has been also shown to be a specific substrate of MMP-1, -3, -13 and -14 but not MMP-8 and -9 [48]. The closely related chemokines CCL2, CCL8 and CCL13 (MCP-1, -2 and -4) are proteolytically cleaved by MMP-1 and -3 (but not MMP-2 and -14) with the truncated products of CCL8 and CCL13 being potent antagonists of the their respective chemokine receptors [48].…”
Section: Mmps In Chemokine Signalingmentioning
confidence: 95%
See 1 more Smart Citation
“…Conceptually, these findings showed that MMPs can not only act as effectors but also regulators of inflammatory responses [47]. Subsequently, CCL7 has been also shown to be a specific substrate of MMP-1, -3, -13 and -14 but not MMP-8 and -9 [48]. The closely related chemokines CCL2, CCL8 and CCL13 (MCP-1, -2 and -4) are proteolytically cleaved by MMP-1 and -3 (but not MMP-2 and -14) with the truncated products of CCL8 and CCL13 being potent antagonists of the their respective chemokine receptors [48].…”
Section: Mmps In Chemokine Signalingmentioning
confidence: 95%
“…Subsequently, CCL7 has been also shown to be a specific substrate of MMP-1, -3, -13 and -14 but not MMP-8 and -9 [48]. The closely related chemokines CCL2, CCL8 and CCL13 (MCP-1, -2 and -4) are proteolytically cleaved by MMP-1 and -3 (but not MMP-2 and -14) with the truncated products of CCL8 and CCL13 being potent antagonists of the their respective chemokine receptors [48]. Apart from influencing the activity of C-C motif chemokines, MMPs also contribute to CXC-chemokine function.…”
Section: Mmps In Chemokine Signalingmentioning
confidence: 99%
“…Which enzyme(s) is responsible for this cleavage, however, is not clear. In the N-terminus, human MCP1 has been reported to be cleaved by matrix metalloproteinase-1, −3, −8, and −12 between aminoacid 4 and 5 (Dean et al, 2008;McQuibban et al, 2002). This cleavage generates a fragment (5-76) that functions as an antagonist for CCR2 (Dean et al, 2008;Gong and Clark-Lewis, 1995;McQuibban et al, 2002;Proost et al, 1998).…”
Section: Microgliamentioning
confidence: 99%
“…In the N-terminus, human MCP1 has been reported to be cleaved by matrix metalloproteinase-1, −3, −8, and −12 between aminoacid 4 and 5 (Dean et al, 2008;McQuibban et al, 2002). This cleavage generates a fragment (5-76) that functions as an antagonist for CCR2 (Dean et al, 2008;Gong and Clark-Lewis, 1995;McQuibban et al, 2002;Proost et al, 1998). Consistently, the MCP1 mutant lacking amino acids 2-8 (7ND) has been shown to inhibit MCP1-CCR2 signaling both in vitro and in vivo (Kitamoto and Egashira, 2003;Ni et al, 2001;Zhang and Rollins, 1995).…”
Section: Microgliamentioning
confidence: 99%
“…The full number of interactions described between MMPs and chemokines is beyond the scope of this review. This mechanism of antagonist-producing chemokine degradation may provide an elegant negative feedback loop that dampens inflammatory cell influx and permits the timely resolution of inflammation [30]. MMP-7 knock-out mice demonstrate a deficit of neutrophil migration that led to the identification of a third mechanism whereby MMPs regulate leucocyte recruitment.…”
Section: Mmps In Normal Immune Responses To Infectionmentioning
confidence: 99%